Penguatan Teori Antrian Pada Pengambilan Dana Bantuan Anak Yatim Dan Muslim Lanjut Usia (MUNSIA) di BAZNAS Provinsi Sumatera Utara - rima aprilia; Della Arsita sari; Ellysa Syahfitri; Mahyuni Br Damanik; Nuriman Astuti Batubara; Dedy Juliandri Panjaitan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
In an effort to build the people's economy, zakat is an important instrument that has great potential, especially for the development and welfare of the economic life of the community. However, this potential must be managed properly and professionally. There are several functions that are carried out, namely planning, implementing and controlling the collection, distribution, and utilization of zakat and reporting accountability for zakat management. The National Zakat Agency is authorized to collect, distribute, and utilize zakat. Community service carried out at Baznas in order to implement a queue system for withdrawing funds for MUNSIA at BAZNAS to help recipients of assistance receive services faster and not experience long waiting times. So to find out the optimal service performance measure in withdrawing funds for orphans and elderly Muslims, a single-track queue system is needed. In the process of serving recipients of MUNSIA at the BAZNAS office, a single-track queue model can be used. Where there is only one path that takes customers to the service stage. The time required by recipients of orphan and munsia aid funds applies the First Come First Served service where customers who come first will be served first. To optimize the service process for recipients of orphan and munsia aid funds, the Model (M/M/1) queuing theory formula can be used. Based on the results obtained, the performance of the queuing system is still optimal because officers are able to provide services to 90% of the arrivals of 55 recipients of orphan and MUNSIA aid funds.